Cardioprotection from intradialytic exercise: a randomized trial - Maufrais, Claire; Josse, Matthieu; Patrier, Laure; Isnard, Myriam; Grandperrin, Antoine; Turc-Baron, Cécile; Nottin, Stéphane; Cristol, Jean-Paul; Boulghobra, Doria; Reboul, Cyril; Obert, Philippe (Nephrology, dialysis, transplantation, 2025)
Left ventricular (LV) regional wall motion abnormalities (RWMAs) related to transient ischemic events are well-documented during hemodialysis (HD). Intradialytic exercise (IDE) reduces the global occurrence of HD-induced RWMAs. However, the regionalization of its cardioprotective effects within the LV wall, and its underlying mechanisms remain unclear. We conducted a prospective, crossover, randomized trial. 72 patients underwent two sessions: standard HD (HD-CONT) and HD with 30min of aerobic exercise (HD-EX). Segmental longitudinal strains (LS) were measured before (T0) and at peak stress (30min before HD-ending, Tpeak). An 18-segment model identified RWMAs, defined as a 20% LS reduction at Tpeak compared to T0. To evaluate the impact of circulating factors, we measured fractional shortening, Ca2+ transients and spontaneous Ca2+ waves (SCaW) following anoxia/reoxygenation (A/R) in isolated rat cardiomyocytes pre-treated with human plasma ultrafiltrates (obtained at Tpeak in both sessions). IDE significantly reduced RWMAs during HD-EX compared to HD-CONT (estimated difference: 1.1 segment, 95%CI: 0.33/1.90, p=0.009). A baso-apical gradient of RWMAs was observed during HD-CONT, with higher prevalence at the apex compared to the base (p=0.03). This gradient was abolished during HD-EX, suggesting greater apical cardioprotection. Pre-treatment of cardiomyocytes with ultrafiltrates from HD-EX improved fractional shortening, Ca2+ handlings and SCaW following A/R compared to cells pre-treated with ultrafiltrates from HD-CONT. IDE limits HD-induced RWMAs, and circulating humoral factors may contribute to this cardioprotection. IDE-induced benefits on RWMAs were greater at the apex. Further studies are needed to elucidate the mechanisms underlying the heterogeneous benefits of IDE on regional myocardial function.